Estar isolado pode afetar o sucesso de polinização? - Maubecin, Constanza Clara (2015)
The spatial distribution of natural plant populations can have different effectson ecological processes and at different scales of operation. In sessile organisms such as plants, each individual in a population experiences a local density variance, which may vary in their influence according to the observed scale. At local scale, the spatial distribution of a population can influence the pollination success, through processes of facilitation or competition. In Parque Estadual Intervales?SP, we assessed the effects of density and size of inflorescences of Vriesea sp. plants on its pollination success. The results showed that the size of the inflorescence had no significant relationship with the conspecific and heterospecific pollen load that reached the stigmas. However, the density of plants Vriesea sp. tends to be related to the conspecific pollen load on flower?s stigmas, as pollination success declined as average distance to the ten nearest conspecifics increased.